Interstitial lung disease in systemic sclerosis (systemic scleroderma) - L. P. Ananyeva; I. E. Tyurin; O. A. Koneva; L. A. Garzanova; A. M. Lila (Современная ревматология, 2021)
In systemic sclerosis (SSc), interstitial lung disease (ILD) is common (>80%) and worsens the prognosis of the disease, but severe progressive damage develops only in 8–10% of cases. Interstitial changes in the lungs occur early (within the first 3–5 years of the disease). The histological manifestations are similar to those of idiopathic ILD.The main tool for screening and diagnosing of ILD associated with SSc is high-resolution computed tomography of the lungs, resulting data influence the choice of therapy. In most patients a relatively intact and stable forced vital capacity of the lungs is recorded for a long time, but the diffusion capacity of the lungs decreases early and steadily. Pulmonary functional tests have prognostic value.The choice of the optimal therapy for SSc with lung lesions is based on general disease activity (the severity of inflammation and fibrosis) and the its severity, rate of progression of the disease in general and the leading pathology – interstitial pneumonia (IP) – in particular. In patients with SSc and severe or progressive IP, treatment with mycophenolate mofetil (MMF), cyclophosphamide, nintedanib, or nintedanib in combination with MMF if appropriate, should be considered. If this therapy is ineffective, rituximab may be used.